MAKNA FILOSOFI WAYANG PURWA DALAM LAKON DEWA RUCI - Eko Setiawan (UIN Sayyid Ali Rahmatullah Tulungagung, 2017)
Wayang is taken from the Javanese language meaning “shadow” or taken the meaning that puppet is the depiction of life or reflection of human nature that exist in human soul itself. Nature itself is divided into two basic nature, the nature of wrath and the nature of goodness. Dewa Ruci story as one of the Wayang plays is a carangan story, which is rich in very deep philosophical and religious values. This story illustrates a man who has a strong will to find the best way that can bring people to happiness. In search of happiness, it is not easy to do because there will be obstacles and obstacles facing. This is where the aesthetic value is packaged in the story of Dewa Ruci and become the main doctrine of the conception of God, humanity, and human relationship with God. The story of Bima in searching the purple mastery tirto pawitrodimahening suci in the story Dewa Ruci philosophically symbolizes how humans must undergo an inward journey to find his identity or search sangkan paraning dumadi the origin and purpose of human life or manunggaling kawula gusti. In this story contained the mandate of the doctrine of human conception, the conception of God, and how man leads to his God.